Potential Nano Gel Extract of Avocute Fruit (Persea Americana Mill) as Alternative in Prevention of Inflammation in White Rats White Rats Post-Extraction Wounds - Yulistina, Yulistina (Journal Research of Social Science, Economics, and Management, 2022)
Complications after tooth extraction include inflammation, bleeding, edema, discomfort, and dry socket. Both nonsteroidal anti-inflammatory drugs (NSAIDs) and steroidal anti-inflammatory drugs are used to treat inflammation. Using chemo drugs is not without side effects. Avocado seed is an herbal substance that is needed as an alternative therapy to reduce wound inflammation caused by tooth extraction. To prove the potential of nano gel (avocado seed extract) and can be applied as an alternative to prevent inflammation in wounds after tooth extraction of white rats. True experiment with randomized posttest with control group design. Consisting of intervention group nano gel avocado seed extract 10%, positive control group povidone iodine 10% and aquadest. Observations were made for 7 days. The variables studied were inflammation of the wound after tooth extraction of rats and histopathological examination (Lymphocytes, Neocapillary and Fibroblasts). According to the unpaired test results, there was no significant difference between the avocado and povidone groups (p=0.143), a significant difference between the avocado and aquadest groups (p=0.001), and a significant difference between the povidone and aquadest groups (p=0.001). p = 0.015). Application of avocado seed extract nanogels at concentrations of 10% and 10% povidone-iodine showed the same ability during wound regeneration and new blood vessel enlargement, and also reduced the number of lymphocyte inflammatory cells, as shown by histology Check confirmed. The administration of nano gel of avocado seed extract is effective and can be applied as an alternative to prevent inflammation in wounds after tooth extraction in white rats.